Are Older Adults with Chronic Musculoskeletal Pain Less Active than Older Adults Without Pain? A Systematic Review and Meta‐Analysis. Issue 9 (6th June 2013) - Stubbs, Brendon; Binnekade, Tarik T.; Soundy, Andy; Schofield, Pat; Huijnen, Ivan P. J.; Eggermont, Laura H. P.
Abstract: Objective: To compare the overall levels of physical activity of older adults with chronic musculoskeletal pain and asymptomatic controls. Review Methods: A systematic review of the literature was conducted using a Cochrane methodology and reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses statement. Major electronic databases were searched from inception until December 2012, including the Cochrane Library, CINAHL, EBSCO, EMBASE, Medline, PubMed, PsycINFO, and the international prospective register of systematic reviews. In addition, citation chasing was undertaken, and key authors were contacted. Eligibility criteria were established around participants used and outcome measures focusing on daily physical activity. A meta‐analysis was conducted on appropriate studies. Results: Eight studies met the eligibility criteria, four of these reported a statistically lower level of physical activity in the older adult sampl e with chronic pain compared with the asymptomatic group. It was possible to perform a non‐heterogeneous meta‐analysis on five studies. This established that 1, 159 older adults with chronic pain had a significantly lower level of physical activity (−0.20, confidence interval 95% = −0.34 to −0.06, p = 0.004) compared with 576 without chronic pain. Conclusion: Older adults with chronic pain appear to be less active than asymptomatic controls. Although this difference was small, it is likely to be clinically meaningful. It is imperative that clinicians encourage older people with chronic pain to remain active as physical activity is a central non‐pharmacological strategy in the management of chronic pain and is integral for healthy aging. Future research should prioritize the use of objective measurement of physical activity.